Implementasi Game Quizizz Sebagai Media Evaluasi Pembelajaran Daring Menyenangkan Di Masa Pandemi Covid-19 - Saiful Bahri; Abdul Mutaleb; Taufik Gunawan; Zamzami Zainuddin (FKIP, Universitas Palangka Raya, 2021)
This study aims to recognize the effectiveness of the game Quizizz implementation in the learning process during the Covid-19 pandemic in the Public Service Management course at the National College of Administrative Sciences, Indonesia. Mixed-method research was employed in collecting the data from students during one semester of the teaching-learning period. Quantitative data were acquired from the results of the “Quizizz”-based assessment (midterm-test) and the final assessment which were analyzed using a t-test. Other quantitative data sourced were derived from questionnaires. These data analyzed students' thoughts and experiences of the advantage of the two applications